Thyroid Collision Tumour: Concurrence of Two Thyroid Malignancy (Bangladesh Medical Journal, 2024)
Thyroid carcinoma is the most common endocrine malignancy. However, it is exceptionally uncommon for two different thyroid malignancies to co-exist within the same thyroid gland. Herein, we present two cases where two different thyroid malignancies present as collision tumours of the thyroid gland. The hypothesis, epidemiology and management are discussed here. Case presentation: Case 1 was a 60 year-old woman presented with an accidental finding of left neck swelling. Ultrasound neck identified multinodular goitre with a suspicious left thyroid nodule. Ultrasound-guided fine-needle aspiration cytology of left thyroid nodule confirms papillary thyroid carcinoma. She underwent total thyroidectomy with central compartment neck dissection. However, histopathology reports a presence of medullary thyroid carcinoma and papillary microcarcinoma in the left thyroid gland. Case 2 was a 59 years old woman presented with left vocal cord paralysis with rapidly enlarging of a long-standing left thyroid swelling. Computed tomography identified bilateral thyroid swelling with left mass causing compression to the trachea and oesophagus. The patient subsequently underwent a total thyroidectomy bilateral central and left selective neck node dissections and left primary non-selective nerve re-innervation. A collision tumour with components of both Hurthle cell carcinoma and papillary microcarcinoma has been shown in histopathology. Collision tumours of the thyroid pose a diagnostic as well as a therapeutic challenge. They should be treated in a multidisciplinary team environment, and the care should be unique to the patient. The treatment should usually be directed by the most aggressive neoplasm.Bangladesh Med J. 2023 Jan; 52(1): 30-34